Molecular Detection of Brucella spp. from Milk of Seronegative Cows from Some Selected Area in Bangladesh. (14th January 2018) - Islam, Md. Sadequl; Islam, Md. Ariful; Khatun, Mst. Minara; Saha, Sukumar; Basir, Md. Samiul; Hasan, Md- Mahmodul
Abstract : Brucellosis is endemic in Bangladesh both in humans and in animals. A number of reasons complicate the diagnosis, as bovine brucellosis can be diagnosed by various serological tests. But the tests have a limitation; when the organism remains intracellular, the disease goes into chronic stage and the antibody titres may decline. The present study was conducted for isolation and detection of Brucella spp. by polymerase chain reaction (PCR) from seronegative cows. A total of 360 dairy cows from three geographical regions were screened serologically by Rose Bengal Plate Test (RBPT) where 24 samples were serologically positive and the rest of the samples were serologically negative. Among the 24 seropositive individuals, 11 were culture positive and 6 were culture positive from serologically negative dairy cows. The overall seroprevalence of brucellosis in cattle was 6.6% and in disease condition a higher prevalence was recorded in abortion (28.07%) followed by infertility (13.33%). To confirm the Brucella spp. in seronegative dairy cattle, the isolates were extracted and PCR was conducted, which produced 905 bp amplicon size of 6 Brucella spp. from milk sample. So, for the detection or eradication of brucellosis, a bacteriological test and a PCR technique should be performed with the serological test of milk.